Development and Pilot Test of the RAND Suicide Prevention Program Evaluation Toolkit - Joie D. Acosta, Rajeev Ramchand (RAND Corporation, 2014)
In response to increasing suicide rates among military personnel, the U.S. Department of Defense (DoD) has implemented many policy changes and invested in a number of programs to prevent suicide within its ranks. The DoD Task Force on the Prevention of Suicide by Members of the Armed Forces (2010) and a subsequent RAND report (Ramchand et al., 2011) both recommended that DoD evaluate existing programs and ensure that new programs include an evaluation component when they are implemented. Evaluations are critical for assessing the impact of DoD investments in suicide prevention and can be used as the basis for decisions about whether to sustain, scale up, or discontinue existing efforts. The Defense Centers of Excellence for Psychological Health and Traumatic Brain Injury (DCoE) asked RAND to draw from the scientific literature and create a toolkit to guide future evaluations of DoDsponsored suicide prevention programs (SPPs). The overall goal of the toolkit is to help those responsible for SPPs determine whether their programs produce beneficial effects and, ultimately, to guide the responsible allocation of scarce resources.